STUDI KINERJA PEGAWAI PT DELTOMED WONOGIRI - Adi Sucipto (JURNAL ILMIAH EDUNOMIKA, 2022)
This study aims to determine the effect of simultaneously (simultaneously) or partially the variables of motivation, discipline, and work environment on the performance of PT Deltomed Wonogiri employees. This research method uses a quantitative descriptive research design. The population is 1,100 employees working at PT Deltomed Wonogiri. The sampling technique used in this research is Quota sampling with a sample size of 100 respondents. Collecting data by using a questionnaire. The data analysis technique used was statistical analysis, namely multiple linear regression, F test, t-test, and the coefficient of determination. The results showed that motivation, discipline, and work environment partially and significantly affected the performance of PT Deltomed Wonogiri employees. Suggestions from this research, employees of PT Deltomed Wonogiri continue to improve motivation, discipline, and the existing work environment so that the employee performance will increase and be better than before. Keywords: Performance, Motivation, Discipline, Work Environment.